PSYCHOLOGICAL FEATURES OF FORMATION OF LEADERSHIP ABILITY AND DEVELOPMENT OF CREATIVE QUALITIES IN STUDENTS - Mardiyeva Shakhnoza Amirovna (Web of Journals Publishing, 2024)
This article highlights the importance of using educational technologies in the formation of leadership skills and development of creative qualities, independent thinking, creative research, and development of creative thinking in students.
Keywords: Leadership ability, traditional leader, organizational leader, creative thinking, education - upbringing, mind, society, spiritually pure, physically healthy, perfect person. The future of our country undoubtedly depends on the development of educated, spiritually mature people of today's generation.